2000
DOI: 10.1177/0093854800027001005
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Treatment-Based Drug Courts in Reducing Criminal Recidivism

Abstract: This study examined outcomes for two treatment-based drug court programs during a 30-month follow-up period. Outcomes for drug court graduates were contrasted with those of nongraduates and of comparison groups that consisted of offenders who were placed on probation supervision during the same period and did not receive drug court services. Drug court graduates from both programs were significantly less likely to be arrested and had fewer arrests during follow-up in comparison to matched probationers and nong… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
118
0

Year Published

2002
2002
2017
2017

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 143 publications
(121 citation statements)
references
References 6 publications
3
118
0
Order By: Relevance
“…Also, note that the protocol defined the drug court-comparison contrast as the primary unit of analysis. Four studies (Goldkamp et al 2000;Peters and Murrin 2000;Rempel et al 2002;Truitt et al 2002) reported findings on more than one such contrast (e.g., different locales). Thus, the 50 unique studies reported results on 55 independent drug court-comparison contrasts.…”
Section: Coding Protocolmentioning
confidence: 99%
“…Also, note that the protocol defined the drug court-comparison contrast as the primary unit of analysis. Four studies (Goldkamp et al 2000;Peters and Murrin 2000;Rempel et al 2002;Truitt et al 2002) reported findings on more than one such contrast (e.g., different locales). Thus, the 50 unique studies reported results on 55 independent drug court-comparison contrasts.…”
Section: Coding Protocolmentioning
confidence: 99%
“…Fortunately that is not the case for all evaluation studies on drug courts. Peters and Murrin (2000), for example, included comparison groups and examined recidivism at 12 months and 30 months (Peters & Murrin, 2000). At 12 and 30 months, graduates were less likely to be arrested than probationers and non-graduates.…”
Section: Drug Court Efficacymentioning
confidence: 99%
“…Generally, drug courts utilize a series of rewards and graduated sanctions to enforce drug court and treatment compliance (Meyer, 2007). It is believed that treatment attendance and compliance, as well as length of time in treatment, will ultimately result in drug addicts who become successful in abstaining from drug use (Peters & Murrin, 2000;Rempel, 2006;Schmitt, 2006). Coercion in the form of jail time is the end point in a regime of graduated sanctions (Harrell, 1998;Meyer, 2007;Satel, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…Unlike the American DTCs [32][33][34], no conclusive outcome evaluation data are available with respect to the Toronto DTC. A quasi-experimental outcome evaluation study was funded by the federal justice department and Fischer/Roberts/Kirst put into operation in 1999, yet critics have proposed that its 'limitations will likely make it impossible to draw definitive conclusions about the effectiveness [of the Toronto DTC] once the results are analysed' [35].…”
Section: Contemporary Compulsory Treatment: the Drug Treatment Courtmentioning
confidence: 99%